Buckling analysis and experimental study of simply-supported single-corrugation steel plates subjected to compression. (March 2022) - Bi, Cheng; Wang, Yan-Bo; Liu, Xiao-Yu; Jiao, Zi-Lun
Abstract: High-strength steels (HSSs) have been increasingly used in construction, resulting in a more thin-walled component plate of steel members. In order to restrain local buckling in high-strength steel tubular columns, an innovative type of corrugated steel plates is proposed in this paper, which is named as the single-corrugation steel plate (SCSP). By utilizing the principle of minimum potential energy, a theoretical derivation is conducted to provide simplified formulas for calculating the elastic buckling stress of simply-supported SCSPs subjected to compression. Based on the parametric analysis, the optimal value of repeating number, trough angle, width and depth of the corrugation are recommended. Then, axial compressive tests are conducted on both L-shaped and T-shaped sections to investigate the buckling behavior of tubular columns composed of the SCSPs. The theoretical formulas are compared with the finite element results (ABAUQS/Buckle), as well as experimental results. The proposed formulas can make reasonable estimation on the buckling resistance of the SCSPs. Graphical abstract: Highlights: The effect of repeating number and trough angle of corrugations on the elastic buckling stress was studied. A theoretical formula for the elastic buckling stress of simply-supported SCSPs subjected to compression was derived. The geometric parameters of the corrugation including aspect ratio, groove width, groove depth and plate thickness were analyzed. Axial compressive tests were conducted on both L-shaped and T-shaped section columns with SCSPs. The proposed resistance formulas were verified against the experimental results.